Systemic exposure to propranolol in patients with chronic liver disease and its correlation with portal blood flow - Kim, Tae-Eun; Kang, Ju-Seop; An, Wen; Sohn, Joo Hyun (Frontiers in Medicine, 2022)
Propranolol is a beta-blocker used for the prevention of variceal bleeding in cirrhotic patients. We investigated the pharmacokinetics of propranolol in patients with chronic liver disease compared to that in healthy individuals. The relative amount of portal blood flow was measured to investigate the correlation of portal blood flow and the systemic exposure of propranolol. Thirty healthy subjects, 18 patients with chronic active hepatitis (CAH), and 54 patients with cirrhosis were included in this prospective study. Blood samples for pharmacokinetic analysis were taken up to 8 h post-dose. The portal blood flow was estimated by H/L ratio using thallium-201 (201TI) per rectal scintigraphy. A total of 78 subjects completed the study. The area under the concentration-time curve (AUC) to the last measurable time (AUClast, ng⋅h/mL) were 150.2 ± 154.1, 112.2 ± 84.7, and 204.0 ± 137.3 in healthy subjects, CAH patients, and cirrhosis patients, respectively. AUCrmlast showed positive correlation with the H/L ratio in patients with chronic liver disease (r = 0.5817, p < 0.0001). In conclusion, the patients with cirrhosis showed higher systemic exposure to propranolol than healthy subjects or patients with CAH. The increase in systemic exposure to propranolol was correlated with the decrease in portal blood flow.